2018
DOI: 10.1186/s12893-018-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful joint preservation of distal radius osteosarcoma by en bloc tumor excision and reconstruction using a tumor bearing frozen autograft: a case report

Abstract: BackgroundThe wrist joint is an extremely rare site for osteosarcoma. Joint structure preservation to maintain good limb function is well described in case of knee osteosarcoma, whereas it is not described in case of wrist joint osteosarcoma. In this report, we present the first case of joint preservation surgery to treat distal radius osteosarcoma using a tumor bearing autograft treated with liquid nitrogen.Case presentationA 46-year-old male presented with swelling and pain in the right wrist and was diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Resection with joint preservation can salvage the majority of wrist function but, as a challenging procedure, it can also lead to an ultra-critical sized bone defect which is technically demanding to reconstruct (5,6). Previous reports regarding wrist joint sparing surgery are rare (7,8). The present study reported a case of wrist preservation surgery using a 3D-printed custom-made porous endoprosthesis after en bloc resection of the EHE in the distal radius.…”
Section: Introductionmentioning
confidence: 79%
“…Resection with joint preservation can salvage the majority of wrist function but, as a challenging procedure, it can also lead to an ultra-critical sized bone defect which is technically demanding to reconstruct (5,6). Previous reports regarding wrist joint sparing surgery are rare (7,8). The present study reported a case of wrist preservation surgery using a 3D-printed custom-made porous endoprosthesis after en bloc resection of the EHE in the distal radius.…”
Section: Introductionmentioning
confidence: 79%
“…With an incidence of 0.3-0.5 per 100,000, osteosarcoma is the most frequent non-hematopoietic primary malignant bone tumor [ 5 ]. According to studies, the distal radius is a common skeletal site for primary bone tumors, but not for osteosarcomas, as only 1% of osteosarcomas are found in the distal radius [ 6 , 7 ]. Uribe-Botero et al [ 8 ] investigated 243 cases with primary osteosarcoma of bone, and they found (49.8%) of tumors arising in the femur to be the first most frequent site, then tibia to be the second most common site, with 47 cases (19.3%), while only one case of distal radius osteosarcoma is recorded.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] While, in this case, the liquid ammonia freezing and inactivating was simple and accurate, which was considered to be a better way to treat tumor bone. 12 This study noted the following points in specific clinical work:…”
mentioning
confidence: 87%